Biological hydrogen production from paper mill effluent via dark fermentation in a packed bed biofilm reactor. (15th April 2023) - Namdarimonfared, Mahboubeh; Zilouei, Hamid; Tondro, Hadiseh
Graphical abstract: Highlights: Evaluation of dark fermentative hydrogen production using paper mill effluent (PME) Investigation of the impact of different HRTs on the biofilm reactor performance. H2 production rate was enhanced to 6.21 L H2 d −1 L −1 by decreasing HRT to 2 h. Max. yield of H2 was 0.96 mmol H2 g −1 COD at 8 h HRT. Production of VFAs as valuable by-products as well as COD removal. Abstract: This study assessed the feasibility of continuous hydrogen production in an anaerobic packed bed biofilm reactor (APBR) using paper mill effluent (PME) without any pretreatment or modification. To form a microbial biofilm on supports, the reactor was seeded with a thermal pretreated anaerobic sludge. After the start-up stage, under mesophilic conditions and pH control, the system performance in the case of hydrogen production as biofuel and VFAs as valuable by-products as well as COD removal was investigated at different hydraulic retention times (HRTs) (24, 16, 12, 8, 4, 2 and 1.2 h). The highest hydrogen concentration in the produced gas was 41.5 % obtained at HRT 4 h. The highest hydrogen production rate and yield were 6.21 L H2 d −1 L −1 at HRT 2 h and 0.96 mmol H2 g −1 COD at HRT 8 h, respectively. With decreasing the HRT from 24 to 1.2 h, the OLR was increased from 27.35 to 547 g COD L −1 d −1 that positively affect the hydrogen production rate for all HRTs except for the shortest HRT. Furthermore, COD removal efficiency was reduced from 25.2 to 6 %. Low value of COD removal efficiency is because of conversion of organic inlet to valuable metabolites such as VFAs in the effluent.